Perbandingan Dosis Open Kinetic Chain Terhadap Perubahan Kemampuan Fungsional Pasien Osteoarthritis Genue di Rumah Sakit Perkebunan Jember Klinik - Tri Chandra Ayu Aprillia; Angria Pradita; Agung Hadi Endaryanto; Fransisca Xaveria Hargiani (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Osteoarthritis is a joint disease in which sufferers experience debilitating cartilage loss, accompanied by abnormal bone development. The causal factor of osteoarthritis itself cannot be known with certainty, but there are several factors that trigger the occurrence of arthritis, including age, gender, obesity, physical activity and continuous work, for example, what happens to athletes running. The recommended exercise is exercise with the Open Kinetic Chain technique which is an active motion training technique without proximal muscle movement and only involves one joint. This study aims to determine the differences in the dose of Open Kinetic Chain on the functional abilities of patients with osteoarthritis genue.This study had 30 respondents with 15 respondents undergoing Open Kinetic Chain for 3 minutes and 15 respondents undergoing Open Kinetic Chain for 5 minutes. The research design uses a quasi-experimental type with a group pretest and posttest approach. Bivariate analysis in this study used the Mann Whitney.The results of this study were that there was no difference in the ratio of the dose of Open kinetic Chain to the functional abilities of patients with osteoarthritis genue at the Perkebunan Jember Klinik Hospital in 2022 with a significance value of the Mann Whitney 0.105> 0.05.This research is expected to increase public knowledge in treating genue osteoarthritis patients with the Open kinetic Chain action and always consult a physiotherapist when complaints occur and wish for physiotherapy.